Gestão ambiental em instituições educação superior no Brasil: o discurso e a realidade - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
The discussions on sustainability and environmental management are a reality in Higher Education Institutions in Brazil. As a result of this, we sought to reveal a panorama of Environmental Management in IES, trying to answer if the discourse in favor of sustainability is configured in actions in the day to day of these organizations. In order to do so, thirty publications in the Capes Periodicals database were evaluated. The results show that despite the seriousness of the environmental problems experienced by humanity and the various commitments assumed through the signing of agreements, the Environmental Management taught is not experienced by IES. The actions practiced are punctual and corrective, they are not structured systematically. The deficiencies also affect Teaching, where the absence of environmental education is perceived in the curricula of undergraduate and postgraduate courses evaluated. It involves Research on the subject that demonstrates that it is necessary to train professionals with the capacity to make decisions based on the consideration of environmental sustainability in their future business and urgently train teachers and researchers with ability to deal with the complexity of the environmental theme. The challenges mentioned range from the complexity involved in the operation of IES, the mental model that the land has an infinite capacity for generating resources and receiving waste, the absurd consensus involving students, employees and teachers who do not question the practices, often harmful to the environment, the myth of the rational university related to the propagation of the idea that these have already reached the highest possible level of functionality, budget constraint, lack of environmental awareness, cultural barriers that vitiate some behaviors, restriction of space for implementing infrastructure for environmental management, institutional demands of other natures considered to be priorities in the short and medium term, lack of recognition of reward for adopting sustainable actions and the belief that governments will solve problems if they become a real risk. The paths pointed out show the need for a change in the way IES works, the commitment of top management, the structuring of environmental management practices, the expansion of studies on the theme, the training of professionals, the approach to the theme in curricula, fostering discussion within and outside its context, strengthening environmental education and disseminating the benefits of an environmental management system. Thus, it is verified that their actions must involve practices consistent with the behaviors and initiatives required by the context of which they are part. They must be aware of the changes that have occurred around them, acting as producers of solutions to the evils faced by society, evidencing the emergence of the global movement to incorporate principles of environmental management into the regiments and practices of Higher Education Institutions.
Environmental management in higher education institutions in Brazil: the discourse and the reality
Keywords: Sustentabilidade; Gestão ambiental; Instituições de educação superior; Mudanças; Stakeholders; Sustainability; Environmental management; Higher education institutions; Changes; CIÊNCIAS HUMANAS: EDUCAÇÃO: ADMINISTRAÇÃO EDUCACIONAL